Measuring participants' immersion in healthcare simulation: the development of an instrument. Issue 1 (January 2016) - Hagiwara, Magnus; Backlund, Per; Söderholm, Hanna; Lundberg, Lars; Lebram, Mikael; Engström, Henrik
Abstract Background Immersion is important for simulation-based education; however, questionnaire-based instruments to measure immersion have some limitations. The aim of the present work is to develop a new instrument to measure immersion among participants in healthcare simulation scenarios. Methods The instrument was developed in four phases: trigger identification, content validity scores, inter-rater reliability analysis and comparison with an existing immersion measure instrument. A modified Delphi process was used to develop the instrument and to establish validity and reliability. The expert panel consisted of 10 researchers. All the researchers in the team had previous experience of simulation in the health and/or fire and rescue services as researchers and/or educators and simulation designers. To identify triggers, the panel members independently screened video recordings from simulation scenarios. Here, a trigger is an event in a simulation that is considered a sign of reduced or enhanced immersion among simulation participants. Results The result consists of the Immersion Score Rating Instrument (ISRI). It contains 10 triggers, of which seven indicate reduced and three enhanced immersion. When using ISRI, a rater identifies trigger occurrences and assigns them strength between 1 and 3. The content validity analysis shows that all the 10 triggers meet an acceptable content validity index for items (I-CVI) standard. The inter-rater reliability (IRR) among raters was assessed using a two-way mixed, consistency, average-measures intra-class correlation (ICC). The ICC for the difference between weighted positive and negative triggers was 0.92, which indicates that the raters are in agreement. Comparison with results from an immersion questionnaire mirrors the ISRI results. Conclusions In conclusion, we present a novel and non-intrusive instrument for identifying and rating the level of immersion among participants in healthcare simulation scenarios.